2023
DOI: 10.1002/nur.22313
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' second victim experience, job insecurity, and turnover intention: A latent profile analysis

Abstract: Nurses are greatly affected by patient safety incidents, but little is known about the classifications of nurses' second victim experiences and their effects on job insecurity and turnover intention. This study aimed to identify the profiles of nurses' second victim experiences, including perceived support and distress, and explore the effects of the different experiences on nurses' job insecurity and turnover intention. A convenience sample of 2000 nurses, who were directly involved in patient safety incident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…According to surveys [4] , there is a 10.0-72.6% prevalence of second victims. It has been demonstrated that nurses experience signi cant stress and injury, which negatively impacts their physical and emotional well-being, their ability to perform well at work, and even heightens their propensity to quit [5] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to surveys [4] , there is a 10.0-72.6% prevalence of second victims. It has been demonstrated that nurses experience signi cant stress and injury, which negatively impacts their physical and emotional well-being, their ability to perform well at work, and even heightens their propensity to quit [5] .…”
Section: Introductionmentioning
confidence: 99%
“…This will allow for easier oversight, correction, and tracking of the incident. To guarantee that solid and trustworthy data are accessible for improvement initiatives, true re ection and prompt reporting are crucial [5] . Though studies have shown that recollection during restoration might create secondary victimization of the second victim, a wellexecuted restoration process can bene t the second victim and lessen the risk of repeat errors [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…Current studies have used quantitative methods to examine the experiences and support of nurses as second victims or qualitative methods. 11 , 12 However, fully understanding the current state of second-victim experience and support with a single quantitative or qualitative study is difficult. Quantitative research can only obtain the second victim’s experience and support scores, and it cannot understand and review personal experiences in depth.…”
mentioning
confidence: 99%